Regional white matter hyperintensities and amyloidosis on domain specific cognition and progression to alzheimer's disease dementia - Choo, Cameron Mavericks (Nanyang Technological University, 2023)
White matter hyperintensities (WMH) have been implicated as a vascular biomarker in accentuating the risk of Alzheimer’s Disease (AD) dementia. However, most of the research conducted previously focused primarily on volumetric global measures of WMHs, leaving regional contributions poorly understood. Moreover, due to overlapping spatial patterns of amyloidosis observed in individuals with AD dementia, region-specific associations between these biomarkers warrant further investigations. Therefore, the present study aimed to elucidate these regional associations and their independent influences on domain-specific cognition. Cox regression models were also used to evaluate the conversion risk of regional WMHs volumes to AD dementia. A total of 196 cognitively normal (CN), 511 with mild cognitive impairment (MCI) and 83 individuals with AD dementia were assessed. In CN and AD dementia groups, regional WMHs were found to predict amyloidosis in the parietal and occipital lobes. Further, regional WMHs played modest roles in predicting cognition in non-demented individuals, with stronger effects on executive function decline. Even after controlling for regional amyloidosis, greater occipital lobe WMHs predicted poorer visuospatial function in those with AD dementia. Lastly, larger occipital lobe WMHs were also significant in predicting conversion to an AD dementia diagnosis. Present results suggest that regional WMHs independently play significant roles in predicting cognitive decline in different domains of cognition. Additionally, higher WMH volumes in the occipital lobe may differentiate AD dementia through pathopsychological symptoms not seen in typical ageing. These findings pave the way for future research to investigate region-specific interventions that address WMH-related symptomology.